2020
DOI: 10.29252/jommid.8.4.127
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antibacterial Activity of Ethanolic Extract of Matricaria chamomilla, Malva sylvestris and Capsella bursa-pastoris against Methicillin-Resistant Staphylococcus aureus

Abstract: The study aimed to determine the antibacterial activity of ethanolic extract of Matricaria chamomilla (chamomile), Malva sylvestris, and Capsella bursa-pastoris against Methicillin-resistant Staphylococcus aureus (MRSA) isolated from clinical specimens. Methods: The plants were collected from Ziarat Village, southern heights of Gorgan, and the required parts were separated and then thoroughly dried in the shade. After grinding, extraction was performed by the maceration method. The extract was dried at 37°C fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
1
12
0
1
Order By: Relevance
“…The results varied depending on the organ used [23][24][25]. Indeed, among 24 S. aureus MRSA studied, ethanolic extracts from flowers had an activity on 20 strains compared to 7 for leaf extracts [23]. The same results were found by Ahani Azari and Danesh [24] against MRSA strains.…”
Section: Antibacterial Activitymentioning
confidence: 80%
See 2 more Smart Citations
“…The results varied depending on the organ used [23][24][25]. Indeed, among 24 S. aureus MRSA studied, ethanolic extracts from flowers had an activity on 20 strains compared to 7 for leaf extracts [23]. The same results were found by Ahani Azari and Danesh [24] against MRSA strains.…”
Section: Antibacterial Activitymentioning
confidence: 80%
“…Several studies reported the antibacterial activity of M. chamomilla ethanolic extracts [117,[138][139][140]. The results varied depending on the organ used [23][24][25]. Indeed, among 24 S. aureus MRSA studied, ethanolic extracts from flowers had an activity on 20 strains compared to 7 for leaf extracts [23].…”
Section: Antibacterial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] Drug-resistant bacteria such as methicillin-resistant Staphylococcus aureus (MRSA), vancomycinresistant Enterococcus (VRE) have emerged as predominant cause of nosocomial infections and can induce a wide spectrum of diseases associated with high morbidity and mortality. [3][4][5][6] Studies have shown that biofilm formation is a common defense mechanism of drug-resistant bacteria, and approximately 65-80 % of bacterial infections are biofilmassociated. [7][8][9] Thus, the development of new antibiofilm agents against S. aureus and E. faecalis has become an urgent task.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria that can resist clinical antibiotics pose a serious threat to public health around the world and bring a great economic burden to human beings [1,2] . Drug‐resistant bacteria such as methicillin‐resistant Staphylococcus aureus (MRSA) , vancomycin‐resistant Enterococcus (VRE) have emerged as predominant cause of nosocomial infections and can induce a wide spectrum of diseases associated with high morbidity and mortality [3–6] . Studies have shown that biofilm formation is a common defense mechanism of drug‐resistant bacteria, and approximately 65–80 % of bacterial infections are biofilm‐associated [7–9] .…”
Section: Introductionmentioning
confidence: 99%